E-207 Venous manometry waveform morphology in idiopathic intracranial pressure without papilledema. (23rd July 2022) - Heiferman, D; Nickele, C; Arthur, A; Goyal, N
Abstract : Introduction/Purpose: Over the past decade, endovascular assessment and treatment of dural venous sinus stenosis (DVSS) has significantly expanded with the growing understanding of its association with idiopathic intracranial hypertension (IIH). Venous manometry has become the standard modality of DVSS evaluation with a trans-stenosis pressure gradient being the recognized metric assessed. In addition to the nominal mean pressures obtained through venous manometry, transduced pressure waveform morphology can provide meaningful physiologic insight into the intracranial environment, as has been understood with Lundberg waves. Venous manometry waveforms upstream from a DVSS have been shown to emulate Lundberg waves, often with P2>P1, suggestive of reduced brain compliance, with normalization of waveforms to a central venous pressure (CVP) morphology downstream. We present two patients with IIH by modified Dandy criteria without papilledema who were found to have a venous waveform suggestive of preserved brain compliance (P1>P2). Materials/Methods: Patient one is a 35 year old Black female who presented with two months of occipital headaches and blurry vision without papilledema. Lumbar puncture opening pressure was 34cmH2O (25mmHg) at the time of venous manometry. Patient two is a 43 year old Caucasian female with two years of retroorbital and occipital headaches and blurry vision without papilledema. Lumbar puncture opening pressure was 32cmH2O (23.5mmHg). She was then started on acetazolamide. Both patients had an empty sella on MRI and bilateral transverse sigmoid junction stenosis on CTA. Through a 0.071 inch inner-diameter catheter in the right jugular bulb, a 160cm length 0.035 inch inner-diameter microcatheter with a 200cm 0.024 inch microwire were navigated through the dural venous system with manometry being performed through the microcatheter at the superior sagittal sinus, torcula, bilateral transverse and sigmoid sinuses, and jugular bulb and veins, noting mean pressures and waveform morphology at each site. Results: Both patients had pressure gradients across bilateral transverse sigmoid junction stenoses, 7mmHg and 14mmHg, respectively, with upstream venous pressures of 17mmHg and 16mmHg, respectively. Both patients had upstream waveform morphologies concordant with Lundberg waves with P1>P2 and a change to CVP morphology downstream. ( Figure 1 ) Conclusion: We postulate that brain compliance can be assessed through venous manometry and there may be correlation to papilledema in IIH. These findings may suggest that DVSS treatment may be considered prior to the onset of papilledema before brain compliance has diminished. However, further prospective studies are needed to assess the impact of our hypothesis on natural history of IIH caused by DVSS. Disclosures: D. Heiferman: None. C. Nickele: None. A. Arthur: None. N. Goyal: None.